Effect E. coli Bacteria Concentration as Self Healing on Compressive Strength and Hydrophobic Properties on Micro Cracks of Concrete - Yolla Octriany; Ratnawulan Ratnawulan (Postgraduate, University of Mataram, 2023)
Buildings are facilities created by humans to support various human activities. Potential damage to old buildings, such as the appearance of cracks in building concrete. Self-healing is carried out by bacteria to repair micro cracks that occur in concrete by deposition of CaCO3. Bacteria-based preservatives consist of bacterial spores and organic compounds that are incorporated into the concrete structure. This research aims to determine the effect of variations in the concentration of E. coli bacteria on compressive strength and contact angle. Based on the results of the research data, two research results can be stated. First, the concentration of bacteria affects the compressive strength of the concrete and the maximum compressive strength occurs on day 14. Second, the concentration of bacteria affects the contact angle of the concrete so that it can be said that the concrete is hydrophobic. As for the XRD characterization, intensity data (I), diffraction angle ( ) were analyzed using High Score Plus. FTIR characterization was carried out in the range 4000 cm-1-500 cm-1. SEM characterization to see the morphology of the concrete with a magnification of 2500 times. SEM can also show E. coli bacteria in concrete